Pemikiran Qiyas dan Implementasinya di Era Modern - Hasan Assidiqi, Ali; Sadiyah, Dini; Mujtahid (Lajnah Ta'lif wan Nasyr Nahdlatul Ulama (LTN-NU) Kabupaten Probolinggo, 2023)
In the midst of modern currents full of new things, it is undeniable that friction between things that have never happened has occurred. With this, Muslims need to be wary because they do not have halal law or not. One of the many foundations of legal establishment is Qiyas. Where Qiyas is used to determine a law if there is no definite proposition that establishes the law so that Qiyas here is one of the solutions used. The purpose of this writing is to explain about qiyas and its application in the modern era. The research method used is library research or literature study with descriptive analysis. The results found that 1) Qiyas is a legal method used by looking at the similarities between the postulates that have problems with problems that occur in the modern era. 2) There are three common types of qiyas including: Qiyas Awlawi, Musawi and Adwan. These three qiyas are actually the same, only the difference lies in the context of the problem. 3) Implementation that can be applied is to know the problem, look for legal propositions that explain the problem, if there are none then look for those that have the same type, then look for similarities and differences and then set the law. An example is about the viral wisky and soju laws, where the related propositions do not exist, but those who talk about the same kind are about khamar because it has in common that it is intoxicating so that the law is haram.